Analysis of Personnel Development in Improving the Quality of Educational Services at MTs Aceh Besar - Dewi Rahmawati; Ismail; Suparta Rasyid (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study analyzes personnel development in improving the quality of educational services at MTs Aceh Besar, including planning, implementation, and evaluation. Descriptive qualitative research was conducted in three madrassas (MTsN 2 Aceh Besar, MTsS Al-Manar, MTsS Lam Ujong) with the subjects of Madrasah Heads, Teachers, and Education Personnel selected by purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and documentation, then analyzed with the NVivo 15-assisted Miles and Huberman model. The results of the study show that personnel development planning begins with needs analysis and participatory work meetings, but is still limited to the short term. The implementation of coaching focuses on service standards, continuous coaching, open communication, and mentoring, but training and teamwork are still weak. Evaluation is carried out through joint assessment, direct supervision, and the use of digital technology, although it is not even and consistent. In conclusion, personnel development at MTs Aceh Besar has contributed positively to improving service quality, but it is still necessary to strengthen long-term strategic planning, structured training programs, and standardization of evaluation so that the principles of Total Quality Management can be optimal and sustainable